Dietary fiber-based floating in situ gels for improved gastric delivery of roselle extract - Saravoot Pumjan, Rachanida Praparatana, Ousanee Issarachot, Ruedeekorn Wiwattanapatapee (Journal of Applied Pharmaceutical Science, 2025)
Dietary fiber-based, in situ gelling systems of roselle extract were formulated to prolong the release of anthocyanin in the stomach. The formulations comprised sodium alginate as a gel-forming polymer (0.5%–1% w/v), and a release rate-controlling polymer (0.25% w/v) selected from hydroxyethyl cellulose, hydroxypropyl methylcellulose, sodium carboxymethyl cellulose, or konjac glucomannan (KGM). Sodium bicarbonate was included as a flotation agent to generate CO2. The formulations showed fast floatation in less than 5 seconds following contact with simulated gastric fluid and stayed afloat for over 8 hours, releasing more than 80% of the anthocyanin content. An increase of sodium alginate concentration resulted in an increment of the gel strength. The optimized formulation containing KGM provided sustained drug release and higher gel strength than other polymers. It also displayed antioxidant activity as evidenced by radical scavenging effects on 2,2-diphenyl-1-picrylhydrazyl. Anti-inflammatory behavior was demonstrated by inhibition of lipopolysaccharide-activated nitric oxide production in RAW264.7 murine macrophage cells, while cytotoxic activity was measured against human gastric carcinoma cells. These results indicate that in situ gelling systems based on dietary fiber derivatives offer potential as a gastroretentive carrier for improving the systemic bioavailability of anthocyanin and for the local treatment of gastric diseases.
Keywords: Roselle, anthocyanin, dietary fibers, oral in situ gels, gastroretentive system